Anatomy of Scale. The Migration Crisis in Europe from the Perspective of Refugee Law and Human Rights Law - Kapelańska-Pręgowska, Julia (University of Wroclaw. Faculty of Law, Administration & Economics, 2018)
Persecution, conflict and poverty forced over a million people to flee to Europe in 2015 and the following years. For the first time after the Second World War, Europe has had to face a so-called migration crisis. This article explores the “anatomy of scale” and its relevance to the existing regimes of international protection for aliens. The application of existing international and EU standards to the “refugees from war” is analyzed, together with issues such as the type of protection granted to these persons and the scope of the principle of non-refoulement and non-rejection at the frontier. The article argues that the system of assessing requests for protection and singling out eligible persons does not work properly in a situation of people coming en masse. This, in fact, technical and practical problem has challenged the whole system and put its underlying principles in question. The article further argues that the temporary protection mechanism is (and will continue to be) a “dead letter” because of lack of solidarity and unanimity. Moreover, it is very difficult to achieve two goals at the same time; that is, to process large numbers of claims for refugee and subsidiary protection and maintain the Dublin Regulation.The article concludes that because mass influx migrations are caused by general factors (usually armed conflict, other internal clashes; in the future probably also natural and humanitarian disasters), a fundamental issue will be to assess the general situation in the country of origin in a coherent and uniform manner. It is recommended that domestic bodies should be given more guidance through legislation or jurisprudence and that the “sliding scale” test, as well as the concept of “sufficient intensity” of general violence and “most extreme cases”, should be further elaborated.
Keywords: kryzys migracyjny; Europa; prawo uchodźcze; prawo praw człowieka